Extra votes to signal loyalty: Regional political cycles and national elections in Russia - Oleg Sidorkin; Dmitriy Vorobyev (Leibniz-Institut für Ost- und Südosteuropaforschung (IOS), 2018)
Under the system of appointing regional governors by the president, which existed in Russia between 2005-2012, governors' loyalty to the central government and particularly their ability to deliver satisfactory results to the ruling party in national-level elections were crucial to their likelihood of being re-appointed for the next term. In this paper, we show that governors, anticipating the relationship between loyalty and re-appointments, attempted to increase their likelihood of being re-appointed by delivering additional votes to the ruling party, and that these attempts were subject to regional political cycles. We argue that delivering satisfactory results may have different importance to a governor depending on the stage of his term at which elections are held. If elections are held close to the expiration of a governor's current term, the results are likely to be pivotal to his further political career. Exploiting variation in the starting and expiry dates of Russian regional governors' terms of office, we find that the winning margins for a pro-government party across Russian regions in national-level elections held between 2007-2012 were substantially higher when elections were closer to the expiration of a regional governor's term. However, for elections held between 1999-2004, when governors were subject to a direct vote by the regional population, no similar effect is found. We then implement several exercises to identify the source of the additional votes for the ruling party and demonstrate that governors, while unlikely using the means of electoral fraud, exerted efforts to stimulate turnout among ruling party supporters.
urn:nbn:de:101:1-2019040811133807131550
Keywords: D72; D73; P26; 330; political cycle; elections; electoral fraud; Russia